Synthesis and characterization of silver nanoparticles using Acremonium borodinense and their anti-bacterial and hemolytic activity. (January 2022) - Nelsonjoseph, Lawrance; Vishnupriya, Benaltraja; Amsaveni, Ramasamy; Bharathi, Devaraj; Thangabalu, Subramani; Rehna, Parameswaran
Abstract: This study explains the mycosynthesis of silver nanoparticles (AgNPs) using Acremonium borodinense by a green route. The synthesized AgNPs were characterized by using UV–vis Spectroscopy, X-ray diffraction spectroscopy (XRD), field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HRTEM) and fourier transform infra-red (FTIR) spectroscopy. XRD technique revealed that the face centered cubic crystalline structure of AgNPs. FE-SEM and TEM images showed that the synthesized AgNPs having spherical shaped nanostructure with an average size of 0.19 nm. The functional groups present in the synthesized AgNPs were studied by FTIR. Mycosynthesized AgNPs were stable up to 3 months without change in their properties. Pathogenic bacteria proliferation was reduced by modest dosages of AgNPs. The minimum inhibitory concentration and minimum bacterial concentration of AgNPs were determined against both gram-positive and gram-negative bacterial pathogens. Such as Staphylococcus aureus, Proteus vulgaris, Serratia marcescens, Klebsiella pneumonia . Highest Value of MIC (90 μg/mL) 0.098 was found against Proteus vulgaris . Antibacterial activity of AgNPs was investigated at three different concentrations based on MIC (30, 60, and 90 g/mL). The impact of AgNPs on Red Blood Cells from the 'O' positive blood group was investigated, and it was shown that even at the highest concentrations, AgNPs does not induce higher hemolysis in the cells. Based on these finding, we strongly suggested that the Acremonium borodinense mediated synthesized AgNPs can be used as a potent bio-medical agent. Graphical abstract: Image 1 Highlights: Mycosynthesized AgNPs were studied and characterized . Acremonium borodinense fungi produced large quantity of metabolites that containing high medicinal value. Fungi mediated synthesis of AgNPs contain less toxicity and more beneficial effect of killing pathogenic bacteria.